The Opportunity of Unified Professional Competence Development for School Teachers Collective - Brikmane, Karīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Teachers’ professional development in Latvia is currently being guided according to the overall mission in education – to create a society, which is engaged in life-long learning. Teaching proficiency and professional growth in teachers’ work are the primary strategies, which to a large extent determine, influence and implement changes in the education sphere. That is why the ongoing development of professional competencies is planned, and results are expected in the goals of the further education programme and in the development of competencies in teachers’ collective.The significance of the research is determined by the need to provide modern, high quality, competitive education for the younger generation. As a consequence, the need for teachers’ ongoing professional development emerges, which is based on the development of competencies appropriate to the time and contemporary methods. Theory and practice have shown that further education is the most effective when it is based on theory, education strategy and real demand/needs.Investment in the development of teachers’ professional growth is one of the most significant resources for improving education quality in the nation. In searching for new and influential resources for the growth and development of teaching competencies, the professional development system and opportunities of practising teachers and schools, and examples of good practice in the promotion of teachers’ professional growth will be analysed.